Bulimia nervosa in female adolescents (Research, Society and Development, 2021)
Bulimia nervosa (BN) is a disease characterized by uncontrolled binge eating. The general objective of the article is to highlight, through a literature review, the importance of nutritional follow-up in the recovery of adolescents with Bulimia Nervosa. It is pointed out that specific objectives are to list how aesthetic patterns affect the way of life of adolescents suffering from Eating Behavior Disorders (ACT), conceptualize bulimia nervosa and its classifications; and highlight the role of good nutrition. To carry out this work, the methodology adopted was a bibliographic survey, of the narrative review type, carried out through scientific articles, obtained through the databases: SciELO, Pubmed, Google academic among other experts who address this subject. The articles published and that are not available free of charge and did not present the full text, articles that were not directly related to the theme, repeated studies, and unpublished research between 2014 and 2021 were ineligible.It is concluded that the factors involved in the maintenance of BN disorder are biological as a genetic predisposition,  Gender. Psychological scans include impulsivity, perfectionism, low self-esteem, among others. Bulimia nervosa implies individualized treatment but accompanied by a multidisciplinary team. Several therapeutic tools can be used for the treatment of patients with bulimia nervosa which includes individualized dietary counseling that ensures an adequate nutritional status.